Morphine electrochemical determination using SnO2 nanostructure-modified glassy carbon electrode in the presence of diclofenac - Isam Ngaimesh Taeb; Zainab S. Hadawi; Rasha N. Alibabery (ADMET and DMPK)
In the present work, SnO2 nanostructures were synthesized and a sensitive voltammetric sensor on a glassy carbon electrode (GCE) was constructed to estimate morphine (MP) in the presence of diclofenac (DLF). Background and purpose: Because diclofenac (DLF) is an NSAID, its administration can reduce postoperative morphine (MP) requirements in adults; for example, standard DLF dosing has been shown to decrease MP use after abdominal surgery. Hence, devising a simple, cost-effective, and swift assay for these compounds in biological and pharmaceutical specimens is indispensable.  Experimental approach: SnO2 nanostructures were synthesized, and a sensitive voltammetric sensor on a glassy carbon electrode (GCE) was constructed to estimate MP in the presence of DLF. Cyclic voltammetry was employed to evaluate the electrochemical response of the SnO2 nanostructures/GCE towards MP. Key results: The SnO2 nanostructures exhibited a significant effect on the electrochemical reaction of the electrode toward the MP oxidation. The SnO2 nanostructures/GCE further exhibited a more sensitive detection platform for MP determination with a limit of detection of 0.006 μM using differential pulse voltammetry in a linear range of 0.01 to 340.0 μM. Conclusion: The SnO2 nanostructures/GCE exhibited extremely high electrochemical activities towards the simultaneous oxidation of MP and DLF. Moreover, the SnO2 nanostructures/GCE provided reproducible and stable responses for MP quantitation. The platform prepared showed successful performance for MP and DLF determination in real samples. SnO2 nanostructures exhibited a significant effect on the electrochemical reaction of the electrode toward the MP oxidation. The SnO2 nanostructures/GCE further exhibited a more sensitive detection platform for MP determination with a limit of detection of 0.006 μM using differential pulse voltammetry in a linear range of 0.01 to 340.0 μM. Additionally, the SnO2 nanostructures/GCE exhibited extremely high electrochemical activities towards the simultaneous oxidation of MP and DLF. Moreover, the SnO2 nanostructures/GCE provided reproducible and stable responses for MP quantitation. The platform prepared showed successful performance for MP and DLF determination in real samples.